Avaliação do Modelo WRF para Aplicação de um índice de Previsão de Geada na Região Sul do Brasil - Bussoni, Caio Vinicius Alves [UNESP]; Moreira, Demerval Soares [UNESP]; Machado, Jeferson Prietsch (Sociedade Brasileira de Meteorologia, 2022)
Understanding the formation processes, as well as the predictability of frosts, is of paramount importance to avoid socioeconomic damage, especially in regions that are prone to the occurrence of the phenomenon, such as in the South and Southeast of Brazil. Among the various methods of forecasting frosts, numerical modeling stands out, which, for this study, used the regional model WRF. This model uses physical parameterizations to represent the sub-grid processes. The WRF allows to choose the parameterization set to be used, in this way, it is possible to evaluate the ones that best reproduce the atmospheric conditions. In this work, the evaluation of the parameterizations was carried out for a set of five cases, covering seven municipalities in the Southern Region of Brazil. The model was executed with grid nesting for three domains: 30, 10 and 3 km of resolution. and for three sets of parameterizations. The result showed that the smallest error was obtained when using the following set of parameterizations: Dudhia for short wave, RRTM for long wave, WDM6 for cloud microphysics and YSU for the planetary boundary layer. Subsequently, a frost index (GI) was applied to the data in order to determine which would better predict the conditions for the occurrence of frost. Again, the same set of parameterizations was better compared to the other sets, showing that the cloud and radiation microphysics have more significant weights in the forecast of the frost phenomenon.

O entendimento dos processos de formação, bem como a previsibilidade das geadas, é de suma importância para evitar prejuízos socioeconômicos, principalmente nas regiões que são propícias a ocorrência do fenômeno, como nas Regiões Sul e Sudeste do Brasil. Dentre os diversos métodos de prever as geadas, destaca-se a modelagem numérica, a qual, para este estudo, utilizou-se o modelo regional WRF. Este modelo permite escolher o conjunto de parametrizações, o que torna possível avaliar aquelas que melhor reproduzem as condições atmosféricas. Neste trabalho a avaliação das parametrizações foi realizada a partir de cinco eventos de geada, abrangendo sete municípios da Região Sul do Brasil. O modelo foi executado com aninhamento de grade para três domínios (30, 10 e 3 km de resolução) e para três conjuntos de parametrizações. O resultado apontou o menor erro quando se utilizou o seguinte conjunto de parametrizações: Dudhia para onda curta, RRTM para onda longa, WDM6 para microfísica de nuvens e YSU para a camada limite planetária. Posteriormente, um índice de geada (IG) foi aplicado para determinar qual melhor conjunto reproduz as condições da ocorrência da geada. O mesmo conjunto de parametrizações mostrou um melhor ajuste, evidenciando que a microfísica de nuvens e a radiação possuem pesos mais significativos na previsão do fenômeno geada.
Evaluation of WRF Model for Application of Frost Forecast Index in the South Brazil
Keywords: regional model; frost; physical parameterizations; modelo regional; geada; parametrizações físicas